The Rarely Vocabulary Used In Batu Belah Area - Azka Ananda Putri; Delviana; Ela Yuhada; Salmah; Yola Rosa (Culture education and technology research (Cetera), 2024)
This article investigates the infrequently used vocabulary in the Batu Belah area through a combined methodological approach of observation and survey. By observing linguistic interactions and administering surveys to local inhabitants, this study aims to identify and analyze words and phrases that are rarely employed in everyday discourse within the region. Through a systematic analysis of survey responses and observational data, we delve into the socio-cultural, historical, and geographical factors contributing to the usage patterns of these lexical rarities. The findings not only provide insights into the linguistic landscape of Batu Belah but also offer a deeper understanding of the preservation and evolution of regional dialects. This research contributes to the broader discourse on linguistic diversity and sheds light on the intricate relationship between language, culture, and identity in the Batu Belah area.